2010
DOI: 10.1007/s10533-010-9547-x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial heterogeneity of understory vegetation and soil in an Alaskan upland boreal forest fire chronosequence

Abstract: In this study we characterized spatial heterogeneity of soil carbon and nitrogen pools, soil moisture, and soil pH of the first 15 cm of the soil profile; depth of the organic horizon; forest floor covers; and understory vegetation abundances in three sites (1999, 1987 and 1920 wildfires) of a boreal forest chronosequence of interior Alaska. We also investigated the cross-dependence between understory vegetation distribution and soil characteristics. Our results showed higher microbial respiration rates and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 49 publications
3
26
1
Order By: Relevance
“…Some previous studies have found increased variation in soil chemistry, e.g. nutrient levels, due to burnings (Harden et al 2004;Lavoie and Mack 2012), but our result suggests that burning with and without clearcutting did not introduce additional variation in the thickness of humus layer to any noticeable degree.…”
Section: Spatial Variability Of Soil and Vegetation Parameterscontrasting
confidence: 68%
See 1 more Smart Citation
“…Some previous studies have found increased variation in soil chemistry, e.g. nutrient levels, due to burnings (Harden et al 2004;Lavoie and Mack 2012), but our result suggests that burning with and without clearcutting did not introduce additional variation in the thickness of humus layer to any noticeable degree.…”
Section: Spatial Variability Of Soil and Vegetation Parameterscontrasting
confidence: 68%
“…We assumed the between-plot spacing of roughly 10 m to produce spatially independent data as the autocorrelation distances for soil and understory vegetation parameters in boreal forests are generally found to be below 10 m (Liski 1995;Smithwick et al 2005;Lavoie and Mack 2012). Thus, here by the term "spatial variability" we mean the variability related to sample locations in a non-autocorrelated dataset.…”
Section: Samplingmentioning
confidence: 99%
“…In savanna-type forests, levels of soil organic matter and nutrients are generally higher below the tree canopy [4,29]. In contrast, in other woodland ecosystems, the absence of fire tends to homogenize the distribution of soil organic matter and nutrients [30][31][32]. It is unknown whether longleaf pine woodlands exhibit strong tree-level spatial patterning of soil nutrients and understory vegetation when burned frequently or whether fire-suppression and woody encroachment alter spatial patterning.…”
Section: Introductionmentioning
confidence: 99%
“…According to Dore et al (2014), a prescribed burn reduces or removes the overstory canopy and more energy reaches the ground, meaning that prescribed burns have a strong effect on the heterogeneity of soil respiration at small scales. Lavoie and Mack (2012) characterized the spatial heterogeneity of soil microbial respiration and the soil carbon pool at three sites that experienced wildfire in years 1999a, 1987a, and 1920a. They found that rates of microbial respiration and microbial biomass were higher at the 1920a sites (longest duration after fire) and that the spatial heterogeneity of soil properties decreased with time after fire.…”
Section: Discussionmentioning
confidence: 99%
“…We used geostatistics and traditional descriptive statistics (CV) to quantify the spatial heterogeneity of soil respiration. According to the literature on the use of geostatistics in ecology (Rossi et al 1992;Dormann et al 2007;Lavoie and Mack 2012), we defined spatial heterogeneity as the integration of two components, spatial variability and patchiness. A soil property has high heterogeneity when it has large spatial variation (high CV) and small patch size (small range a).…”
Section: Introductionmentioning
confidence: 99%